LINT, a Novel dL(3)mbt-Containing Complex, Represses Malignant Brain Tumour Signature Genes. - Meier, K.; Mathieu, E.L.; Finkernagel, F.; Reuter, L.M.; Scharfe, M.; Doehlemann, G.; Jarek, M.; Brehm, A. (PLoS Genetics, 2012)
Mutations in the l(3)mbt tumour suppressor result in overproliferation of Drosophila larval brains. Recently, the derepression of different gene classes in l(3)mbt mutants was shown to be causal for transformation. However, the molecular mechanisms of dL(3)mbt-mediated gene repression are not understood. Here, we identify LINT, the major dL(3)mbt complex of Drosophila. LINT has three core subunits-dL(3)mbt, dCoREST, and dLint-1-and is expressed in cell lines, embryos, and larval brain. Using genome-wide ChIP-Seq analysis, we show that dLint-1 binds close to the TSS of tumour-relevant target genes. Depletion of the LINT core subunits results in derepression of these genes. By contrast, histone deacetylase, histone methylase, and histone demethylase activities are not required to maintain repression. Our results support a direct role of LINT in the repression of brain tumour-relevant target genes by restricting promoter access.